2022
DOI: 10.3390/tropicalmed8010027
|View full text |Cite
|
Sign up to set email alerts
|

SafeHANDS: A Multimodal Hand Hygiene Intervention in a Resource-Limited Neonatal Unit

Abstract: Background: Hand hygiene (HH) is a cornerstone of programmes to prevent healthcare associated infections (HAI) globally, but HH interventions are seldom reported from African neonatal units. Methods: We conducted a quasi-experimental study evaluating the impact of a multi-modal intervention (SafeHANDS) on HH compliance rates, alcohol-based handrub (ABHR) usage, the Hand Hygiene Self-Assessment Framework (HHSAF) score, and healthcare-associated bloodstream infection (HA-BSI) rates at a 132-bed South African neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Other studies in general medicine have shown that although HH awareness exists, compliance is low. [27][28][29][30][31] New strategies to strengthen HH compliance, including implementation science and behavioural modification adapted to context, could be part of the solution. 32 The other IPC components explored: pharmacy management protocols, patient environment, clean dirty circuit protocol and waste management, declared present in 40%-70% of structures, could be a target for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in general medicine have shown that although HH awareness exists, compliance is low. [27][28][29][30][31] New strategies to strengthen HH compliance, including implementation science and behavioural modification adapted to context, could be part of the solution. 32 The other IPC components explored: pharmacy management protocols, patient environment, clean dirty circuit protocol and waste management, declared present in 40%-70% of structures, could be a target for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…36 same study demonstrated that, in practice, the volume of alcoholic preparation used per HH opportunity in the National Health Service (NHS) is probably closer to 1 ml. 27 In a multimodal intervention in South Africa, the reference of 3 ml per HH opportunity was also used for measurement 28 and, likewise, in the context of Primary Care in the Faranah region, Guinea. In this analysis, a clear underutilization was identified, with an average of 0.77 ml per consultation, compared to the recommended minimum amount of 3 ml per HH 29 .…”
Section: Authors and Journalmentioning
confidence: 99%